How 25(OH)D Levels during Pregnancy Affect Prevalence of Autism in Children: Systematic Review - Ucar, Nazli; Grant, William B.; Peraita-Costa, Isabel; Morales Suarez-Varela, Maria (MDPI, 2020)
Autism spectrum disorder (ASD) is a group of dysfunctions in social interaction, communication, and behaviors. The etiology of ASD is not yet fully understood

however, it consists of the interaction between genetics and the environment. An increasing amount of evidence points to the possibility that gestational and early-childhood vitamin D deficiency may be involved in the etiology of some cases of ASD. Herein, we systematically review the literature for studies on vitamin D status during pregnancy and ASD outcomes. Forty-three studies in the PubMed and 124 studies in EMBASE databases were initially found. After screening, 26 were identified as candidate studies for inclusion. Finally, 14 articles met the inclusion criteria, which originated from nine countries. The studies included 10 original research studies and four review studies conducted between 2012 and 2020. The strength of evidence that vitamin D levels during pregnancy increase the risk of developing autism is very low. This is because the evidence relies exclusively on observational studies that did not equally consider all important confounders and that assessed the indirect relationship between vitamin D as a surrogate for sunlight exposure and autism risk. The findings of this systematic review are consistent with the hypothesis that low vitamin D levels might contribute to the development of autism. However, we must also recognize the possible confusion bias and therefore experimental studies with very large sample sizes, given incidence of autism, that allow us to detect blood levels in pregnant women would be helpful to clarify this point.
Keywords: hedging; transaction costs; dynamic programming; risk management; post-decision state variable